2019
DOI: 10.3390/biom9120808
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Terpene Synthase from Tea Green Leafhopper Being Involved in Formation of Geraniol in Tea (Camellia sinensis) Leaves and Potential Effect of Geraniol on Insect-Derived Endobacteria

Abstract: When insects attack plants, insect-derived elicitors and mechanical damage induce the formation and emission of plant volatiles that have important ecological functions and flavor properties. These events have mainly been studied in model plants, rather than crop plants. Our study showed that tea green leafhopper (Empoasca (Matsumurasca) onukii Matsuda), a major pest infesting tea attack significantly induced the emission of geraniol from tea leaves, but did not affect the crude enzyme activity of geraniol syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Furthermore, HIPVs might influence insect feeding physiology by regulating microbes [130] , [131] . Tea green leafhopper has also been found to induce geraniol release, but has no effect on the activity of geraniol synthase (GS) in tea leaves [132] . However, GS from tea green leafhopper can induce geraniol formation in tea plants, suggesting that the protein from this insect might be the main factor.…”
Section: Why Tea Plants and Tea Green Leafhoppers Have A Symbiotic Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, HIPVs might influence insect feeding physiology by regulating microbes [130] , [131] . Tea green leafhopper has also been found to induce geraniol release, but has no effect on the activity of geraniol synthase (GS) in tea leaves [132] . However, GS from tea green leafhopper can induce geraniol formation in tea plants, suggesting that the protein from this insect might be the main factor.…”
Section: Why Tea Plants and Tea Green Leafhoppers Have A Symbiotic Relationshipmentioning
confidence: 99%
“…Furthermore, geraniol inhibited the endobacteria isolated from tea green leafhoppers in vitro . Therefore, during attack, tea green leafhoppers are speculated to use their own GS to enhance geraniol formation in tea plants, with the produced geraniol then being able to affect the insect physiological activity by mediating the growth of its endobacteria [132] .…”
Section: Why Tea Plants and Tea Green Leafhoppers Have A Symbiotic Relationshipmentioning
confidence: 99%
“…Even geraniol has been reported in numerous medicinal plants, for instance, Pelargonium graveolens L'Hér. ( Gupta et al, 2001 ), Camellia sinensis (L.) Kuntze ( Zhou et al, 2019 ), Rosa × damascena Herrm. ( Sadraei et al, 2013 ), Cymbopogon flexuosus (Nees ex Steud.)…”
Section: Natural Products Against Sars-cov-2: Computational To Preclinical Studiesmentioning
confidence: 99%
“…However, no geraniol synthase ( GES ) genes have been identified in tea plants, while many GES genes have been found in other plant species ( Degenhardt et al, 2009 ). Interestingly, it was once suggested that a leafhopper geraniol synthase was likely contributing to tea geraniol production and the characteristic aroma of “Oriental Beauty” tea ( Zhou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%